Changes in ER, PR, HER2, and Their Association With Disease Outcome in Invasive Breast Carcinoma (IBC) Patients Post-Neo Adjuvant Chemotherapy (NAC) and Surgery. - Ravishankar, Monisha C; Toi, Pampa Ch; Dubashi, Biswaji; Dharanipragada, Kadambari (Breast Cancer: Basic & Clinical Research, 2025)
Background: Estrogen-receptor (ER), progesterone-receptor (PR), and human epidermal growth factor-2 (HER2) are performed on pre-neoadjuvant chemotherapy (NAC) biopsies of invasive breast carcinoma (IBC). However, they are not done routinely on post-NAC IBC with residual tumor. Objectives: This study helps in understanding the effect of alteration in expression of ER, PR, and HER2 in pre and post NAC IBC with residual tumors in terms of disease outcome, such as disease-free survival (DFS) and overall survival (OS). Design: This was a Cohort study (Prospective and Retrospective Cohort). Methods: All newly diagnosed cases of IBC who had undergone surgery after NAC with pre-NAC biopsies available with residual tumors in the breast, from January 2017 to January 2020 were enrolled in the study (n = 174) and were followed up till July 2022. Results: There were 174 cases included in this study. Of the 174 cases, 77 (44%) ER+ cases turned −ve, 10 ER +ve cases remained +ve and 87(50%) cases which were ER−ve remained the same. 48(27%) of PR +ve cases turned −ve, 10 PR +ve cases remained +ve and 116 (67%) cases remained −ve. 64(36%) of HER2 +ve cases turned −ve, 4 (2%) of HER2 +ve cases remained +ve; whereas 103(59%) cases remained −ve. The cases with changes in ER and HER2 status from positive to negative showed a longer DFS and OS which was statistically significant. Conclusion: There is a change in the HR and HER2 status in cases of IBC with residual tumor post NAC and patients with changes in the receptor status post-NAC have a better OS and DFS than those whose receptor status do not show a change. Plain Language Summary: Changes in ER, PR, HER2 and Their Association with Disease Outcome in Invasive Breast Carcinoma (IBC) Patients Post-Neo Adjuvant Chemotherapy (NAC) and Surgery Introduction: Estrogen-receptor (ER), progesterone-receptor (PR), and human epidermal growth factor-2 (HER2) are performed on pre-neoadjuvant chemotherapy (NAC) biopsies of invasive breast carcinoma (IBC). However, they are not done routinely on post-NAC IBC with residual tumor. This study helps in understanding the effect of alteration in expression of ER, PR, and HER2 in pre- and post-NAC IBC with residual tumors in terms of disease outcome, such as disease-free survival (DFS) and overall survival (OS). Methods: This was a Cohort study (Prospective and Retrospective Cohort). All newly diagnosed cases of IBC who had undergone surgery after NAC with pre-NAC biopsies available with residual tumors in the breast, from January2017 to January 2020 were enrolled in the study (n = 174) and were followed up till July 2022. Results: There were 174 cases included in this study. Of the 174 cases, 77 (44%) ER + cases turned −ve, 10 ER +ve cases remained +ve and 87(50%) cases which were ER−ve remained the same. 48 (27%) of PR +ve cases turned −ve, 10 PR +ve cases remained +ve and 116 (67%) cases remained −ve. 64 (36%) of HER2 +ve cases turned −ve, 4 (2%) of HER2 +ve cases remained +ve; whereas 103 (59%) cases remained −ve. The cases with changes in ER and HER2 status from positive to negative showed a longer DFS and OS which was statistically significant. Conclusion: There is a change in the HR and HER2 status in cases of IBC with residual tumor post NAC and patients with changes in the receptor status post-NAC have a better OS and DFS than those whose receptor status do not show a change.